Multi-Walled Carbon Nanotubes Solid-Phase Extraction and Capillary Electrophoresis Methods for the Analysis of 4-Cyanophenol and 3-Nitrophenol in Water - Zeid A. ALOthman; Ahmad Yacine Badjah; Marcello Locatelli; Imran Ali (Molecules, 2020)
Analysis of 4-cyanophenol and 3-nitrophenol was carried out using multi-walled carbon nanotubes-based solid-phase extraction (SPE) and capillary electrophoresis (CE) methods. Capillary electrophoresis was carried out with 18 kV voltage, 214 nm detection, and phosphate buffer (pH 7.0, 15 mM) as background electrolyte at 25 ± 1 °C temperature with 15.05 and 16.5 min migration times of 4-cyanophenol and 3-nitrophenol. The separation and resolution factors were 1.10 and 2.90. The optimized experimental conditions were 40 mg/L concentration, 1.0 g multi-walled carbon nanotubes (MWCNTs) per SPE cartridge, 5.0 mL/min flow rate of water, 0.1 mL flow rate of eluting solvent. The maximum recoveries were 91% and 98% at 0.1 mL/min flow rate of 4-cyanophenol and 3-nitrophenol. These methods were applied successfully for extraction and estimation of 4-cyanophenol and 3-nitrophenol in the municipal wastewater. The reported methods are reproducible, efficient, and practical for the estimation of these phenols in water.